Manejo de pseudomonas solanacearum E.F Smith con enmiendas y microorganismos antagonistas en tomate - Díaz Blandón, Jorge U. (CATIE, Turriaba (Costa Rica), 2020)
Tesis (Mag Sc)--CATIE, Turrialba (Costa Rica) 1999